SURVEILLANCE AND GUARDIANSHIP ATTITUDES: ROLE OF MULTIPLE MEDIATORS - Marzbali, Massoomeh Hedayati; Abdullah, Aldrin; Maghsoodi Tilaki, Mohammad Javad (PLANNING MALAYSIA, 2020)
Urban design researchers and environmental criminologists believe that personal and situational characteristics influence how and when residents act as guardians over where they live. However, little is known about the individual factors that explain residential guardianship behaviours. This study focuses on sociophysical factors in explaining residents’ willingness to act as guardians to control criminal behaviour through multiple mediators. A sample of 247 residents in Penang, Malaysia was analysed via structural equation modelling. Results demonstrated that although no significant direct association exists between natural surveillance and guardianship, this relationship was mediated via territorial identity and increases in social cohesion. Findings also indicated the significant role of territorial identity, perceived risk and social cohesion in explaining the amount of guardianship attitude. Furthermore, surveillance helps reduce perceived risk among residents. Social cohesion is the most influential factor in shaping the opportunity for capable guardianship in the study area. It is concluded that organising community-based activities will help strengthen community ties, thereby creating substantial willingness among residents to intervene for the common good and building safer communities. Using extensive survey data from a multi-ethnic community in Malaysia, this study brings to the fore the ways in which the sociophysical factors help foster guardianship attitudes within residential contexts using multiple mediators.